Menata Desa Bersama GEN PADI: Model Edukasi Partisipatif Pencegahan Pernikahan Usia Dini di Desa Tutuyan Induk - Irne Wida Desiyanti; Fauzan H. Doe; Aiska F. C. Karim; Putri N. Latief; Amalya Kurnia; Ni Kadek P. Wibuti; Adelia P. Saleh; Anastasya Mahmud (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Early marriage affects adolescents’ reproductive health, educational continuity, and social well-being. This community engagement activity aimed to describe the implementation of GEN PADI (Generasi Peduli Anti Pernikahan Dini) as a participatory education model in Tutuyan Induk Village. Methods: The one-day activity was conducted with SMAN 1 Tutuyan and the Tutuyan Induk Village Government, involving 36 students, comprising 14 boys and 22 girls. The intervention included outreach, reproductive health education, future-planning literacy, interactive discussion, and collaborative advocacy. Evaluation used observation, group discussion, and an evaluation questionnaire. Because documentation of the instrument, scoring procedure, and individual pre-test–post-test scores was unavailable, the analysis was limited to a descriptive account of the implementation process and participant responses. Results: The activity was interactive. Participants were able to identify health, educational, psychosocial, and economic risks, as well as internal and external factors associated with early marriage. Active participation indicated initial engagement; however, it cannot be interpreted as a quantified improvement in knowledge or attitudes. Conclusions: GEN PADI is feasible as an initial school- and village-based participatory education model. Further evaluation should use validated instruments and properly documented pre-test–post-test data.